Las dos caras del protagonista en Los Persas de Esquilo - García Novo, Elsa (Cuadernos de Filología Clásica. Estudios griegos e indoeuropeos, 2005)
Aeschylus found a peculiar way of attaching heroic virtues to the powerful Persian people, in order to fashion a suitable rival to Greece. A powerful enemy was not enough; they had to be righteous and conscious of their limits. In this way the defeat would make the winners truly great. Therefore the poet created a double-faced King. The deceased Darius is presented as a hero and invoked as a god: he was well aware of sophrosyne, he respected divinity and everything he did was right. On the other hand, Xerxes, out of hybris, provoked death and destruction, relying solely on his own abilities. The Persian people were not the ones to blame. It was just the leader’s wrong decision. Fromanother perspective, Aeschylus has spread the defeat throughout the play by means of three catalogues. In the anapaestic parodos the chorus displays the powerful army, naming the captains who went to attack Greece: first catalogue. Further on, the messenger proclaims the news of the defeat, and enumerates (302 ff.) a second catalogue of captains, dead ones this time. It is the counterpart of the parodos’ catalogue. The entrance of Xerxes alone (the only chief who escaped death), is followed by a lyric dialogue with the chorus (chorus leader), where the King is forced to list the names of the captains whose death he provoked: third catalogue. A deadly ring attaches parodos and exodus.
Keywords: Greek Tragedy; Aeschylus; Persians; catalogues; characters; Heroic Dareius/Xerxes hybristès